British Literature II Romantic Era to the Twentieth Century and Beyond - Robinson, Bonnie J. (Open textbook library., 2018)
The University of North Georgia Press and Affordable Learning Georgia bring you British Literature II: Romantic Era to the Twentieth Century and Beyond. Featuring 37 authors and full texts of their works, the selections in this open anthology represent the literature developed within and developing through their respective eras. This completely-open anthology will connect students to the conversation of literature that has captivated readers in the past and still holds us now. Features: Contextualizing introductions to the Romantic era; the Victorian era; and the Twentieth Century and beyond Over 90 historical images In-depth biographies of each author Instructional Design features, including Reading and Review Questions This textbook is an Open Educational Resource. It can be reused, remixed, and reedited freely without seeking permission.